Early clues regarding the pathogenesis of long-COVID. Issue 4 (April 2022) - Peluso, Michael J.; Deeks, Steven G.
Abstract : Intense investigation into the predictors and determinants of post-acute sequelae of SARS-CoV-2 infection (PASC), including 'long COVID', is underway. Recent studies provide clues to the mechanisms that might drive this condition, with the goal of identifying host or virus factors that can be intervened upon to prevent or reverse PASC.